2015
DOI: 10.5152/ucd.2013.43
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous idiopathic pneumoperitoneum with acute abdomen

Abstract: Pneumoperitoneum is often caused by visceral perforation, and usually manifests with symptoms of peritonitis requiring surgical intervention. Non-surgical spontaneous pneumoperitoneum (ie. not associated with organ perforation) is a rare entity due to intrathoracic, intra-abdominal, gynecologic, iatrogenic or other reasons, and is usually treated conservatively. Idiopathic spontaneous pneumoperitoneum is even rarer than visceral perforation or other causes of free intra-abdominal air. In this report, we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
0
11
0
2
Order By: Relevance
“…If abdominal pain and distension are minimal, and peritoneal signs, fever, and leukocytosis are absent, conservative management should be considered for nonsurgical pneumoperitoneum [12]. However, spontaneous pneumoperitoneum poses significant management dilemmas for surgeons, especially when peritoneal signs are present [13,14]. Although Tani et al suggested that conservative treatment may be applicable for spontaneous pneumoperitoneum with peritoneal signs, exploratory laparotomy should be considered when signs and symptoms of peritonitis are present [15].…”
Section: Discussionmentioning
confidence: 99%
“…If abdominal pain and distension are minimal, and peritoneal signs, fever, and leukocytosis are absent, conservative management should be considered for nonsurgical pneumoperitoneum [12]. However, spontaneous pneumoperitoneum poses significant management dilemmas for surgeons, especially when peritoneal signs are present [13,14]. Although Tani et al suggested that conservative treatment may be applicable for spontaneous pneumoperitoneum with peritoneal signs, exploratory laparotomy should be considered when signs and symptoms of peritonitis are present [15].…”
Section: Discussionmentioning
confidence: 99%
“…Intra-thoracic causes include thoracic trauma (such as barotrauma), post-cardio-pulmonary resuscitation and excessive mechanical ventilation with high peak inspiratory pressures [7,8]. In these cases, pneumoperitoneum is usually a result of raised intra-thoracic pressure, which leads to the leakage of intrathoracic air through microscopic pleural and diaphragmatic defects, and pneumomediastinum often co-exists [2]. In such cases, management of pneumoperitoneum is typically conservative [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic pneumopertoneum (IP) is a rare clinical entity [[1], [2], [3], [4], [5]]. In over 90% of cases, pneumoperitoneum is due to hollow viscus perforation, usually requiring urgent surgical intervention [1,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations